2000
DOI: 10.1016/s0886-3350(00)00520-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of ultrasound biomicroscopy in managing pseudophakic pupillary block glaucoma

Abstract: We describe a case of anterior capsule adherence to the iris that occurred after phacoemulsification with in-the-bag intraocular lens (IOL) implantation. This adherence led to the development of pseudophakic pupillary block glaucoma. There were no synechias at the pupillary margin associated with the capsule-iris adherence. Ultrasound biomicroscopy, used to evaluate the anterior segment in vivo, clarified the mechanism of pseudophakic pupillary block. The pupillary block was relieved by a single laser iridotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…7 This technique has been used to determine IOL positioning in the past and to elucidate the cause of reverse pupillary block. 810 In a case study by Sathish et al, 10 anterior segment UBM helped to diagnose iris bombe as the cause of pseudophakic pupillary block glaucoma 3 years after implantation of a 3-piece IOL in the bag 8 . In our case, while the configuration of the haptic provided a clue as to the etiology of pupillary block, anterior segment UBM confirmed that the IOL was causing anterior bowing of the iris and helped to exclude other causes such as aqueous misdirection syndrome, 11 bilateral ring cysts of the ciliary body, 8 late-onset secondary pigmentary glaucoma, 9 a thick Soemmerring ring, and anterior displacement of the ciliary body.…”
Section: Discussionmentioning
confidence: 99%
“…7 This technique has been used to determine IOL positioning in the past and to elucidate the cause of reverse pupillary block. 810 In a case study by Sathish et al, 10 anterior segment UBM helped to diagnose iris bombe as the cause of pseudophakic pupillary block glaucoma 3 years after implantation of a 3-piece IOL in the bag 8 . In our case, while the configuration of the haptic provided a clue as to the etiology of pupillary block, anterior segment UBM confirmed that the IOL was causing anterior bowing of the iris and helped to exclude other causes such as aqueous misdirection syndrome, 11 bilateral ring cysts of the ciliary body, 8 late-onset secondary pigmentary glaucoma, 9 a thick Soemmerring ring, and anterior displacement of the ciliary body.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, a 2003 ASCRS survey 2 showed that 72% of small incision cataract surgery was performed through a clear corneal section with only 28% through a scleral tunnel (no UK data available). The cohort of Lindfield et al 1 had a disproportionately high percentage of scleral tunnel patients compared with likely current standard practice.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…The value of HFU in cases of pseudophakic pupillary block and other post-operative ciliary body abnormalities was demonstrated by us in previous publications. 2,3 Anterior segment OCT is an 'optical scan' and therefore obeys the simple optical principle of inability to penetrate through opaque media. This is the domain of ultrasound.…”
mentioning
confidence: 99%
“…Laser peripheral iridotomy will result in iris flattening by relieving the anterior–posterior chamber pressure differential. UBM has been shown to be of value in elucidating the etiology of pupillary block glaucoma [34,36,37]. UBM can also be useful for the diagnostic imaging of malignant glaucoma (Figure 4), which is characterized by a forward movement of the iris–lens diaphragm and a very shallow anterior chamber, typically following glaucoma surgery, chronic angle-closure glaucoma or pseudoexfoliation [38].…”
Section: Clinical Application Of Ubm and As-oct For Glaucoma Diagnosis mentioning
confidence: 99%